Assessing the regional socio-economic impact of the European R&I programme - Martin Christensen (European Commission, Joint Research Centre (JRC), 2018)
Structural socio-economic differences across EU regions may result in heterogeneous regional responses to changes in public spending in support to R&I. In this paper we examine the socio-economic impact at the EU aggregate level and at the regional level of alternative policy designs of the future EU R&I support programme that will be put in place after 2020. For the analysis we use the RHOMOLO spatial CGE model covering 267 EU regions. Our results indicate that public spending in support to R&I can contribute to higher aggregate GDP and employment in the EU. However, the impact of public spending in support to R&I varies considerable across regions. The R&I intensive regions benefit the most in terms of GDP and employment while other regions may suffer from a shift in public spending towards R&I support programmes.
Keywords: 330; region; growth; Horizon Europe; Research and Innovation; impact assessment; RHOMOLO